Economic globalisation, inequality and the role of social protection - Bergh, Andreas (OECD Publishing, 2017)
This paper examines the link between economic globalisation, social protection expenditure, and within-country income inequality. We examine the relationship using income inequality data from both the Luxembourg Income Study (LIS) and the Standardized World Income Inequality Database (SWIID). The results based on the LIS data confirm previous findings that economic globalisation, especially economic flows, associates with higher income inequality, and that social protection expenditure are negatively associated with inequality
Keywords: Development